Meta-Analysis: Effects of Adolescent's Knowledge, Attitude, and Parental Support, on Human Papilloma Virus Immunization Uptake - Wiwit Marliana; Uki Retno Budihastuti; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: Human papillomavirus (HPV) is one of the most common sexually transmitted viruses worldwide. HPV vaccination coverage is still low, especially for adolescents, some influential factors are lack of knowledge, rejection, and support of the closest environment in receiving vaccination services. This study aims to estimate the effect size of knowledge, attitudes, and parental support on the use of HPV immunization services in adolescents. Subjects and Method: A systematic review and meta-analysis study using PRISMA diagrams. The article search was conducted based on eligibility criteria with the PICO Model. Population: female adolescents, Intervention: high knowledge, positive attitude, strong parental support, Comparison: less knowledge, negative attitude, poor parental support, Outcome: Use of HPV immunization services. The articles used were from Google Scholar, Europe PMC, PubMed, and Science Direct published from 2016 – 2023. The keywords used in the search were “adolescent